2019
DOI: 10.1101/838482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PHGDH supports liver ceramide synthesis and sustains lipid homeostasis

Abstract: Background D-3-phosphoglycerate dehydrogenase (PHGDH), which encodes the first enzyme in serine biosynthesis, is overexpressed in human cancers and has been proposed as a drug target. However, whether PHGDH is critical for the proliferation or homeostasis of tissues following the postnatal period is unknown. Methods To study PHGDH inhibition in adult animals, we developed a knock-in mouse model harboring a PHGDH shRNA under the control of a doxycycline-inducible promoter. With this model, PHGDH depletion can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In addition, humans with hypomorphic mutations in PHGDH exhibit developmental delays that can be ameliorated by serine supplementation, suggesting that transitory PHGDH inhibition following completion of neuronal development may be tolerable. Moreover, a recent study found that systemic depletion of PHGDH was well tolerated in multiple highly proliferative tissues in adult mice (76). These results suggest that PHGDH inhibitors may be well tolerated, provided that adequate serine and glycine are available in the diet.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, humans with hypomorphic mutations in PHGDH exhibit developmental delays that can be ameliorated by serine supplementation, suggesting that transitory PHGDH inhibition following completion of neuronal development may be tolerable. Moreover, a recent study found that systemic depletion of PHGDH was well tolerated in multiple highly proliferative tissues in adult mice (76). These results suggest that PHGDH inhibitors may be well tolerated, provided that adequate serine and glycine are available in the diet.…”
Section: Discussionmentioning
confidence: 85%
“…Among these tissues, the expression and activity of the phosphorylated pathway in the liver are regulated by systemic levels of protein/amino acid nutrition and hormones [ 7 , 8 ]. Recent studies have implicated that Phgdh-dependent Ser synthesis supports general lipid homeostasis [ 9 ] and appears to prevent non-alcoholic fatty liver disease [ 10 , 11 , 12 ]. Nonetheless, it remains unclear how de novo Ser synthesis via the phosphorylated pathway contributes to the physiological function of the liver at steady state.…”
Section: Introductionmentioning
confidence: 99%